2010
DOI: 10.1073/pnas.0909329107
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of fruit shelf life by suppressingN-glycan processing enzymes

Abstract: In a globalized economy, the control of fruit ripening is of strategic importance because excessive softening limits shelf life. Efforts have been made to reduce fruit softening in transgenic tomato through the suppression of genes encoding cell wall-degrading proteins. However, these have met with very limited success. N-glycans are reported to play an important role during fruit ripening, although the role of any particular enzyme is yet unknown. We have identified and targeted two ripening-specific N-glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(191 citation statements)
references
References 40 publications
12
178
0
1
Order By: Relevance
“…Finally, phospholipase D causes membrane deterioration through catalyzing the hydrolysis of phospholipids, which maintain cell viability and homeostasis into phosphatidic acid (Dawidowicz 1987;Exton 1997). Suppressing such enzymes in fruit tissues considerably reduces softening rate, improve fruit quality, and extend shelf life (Brummell et al 1999;Sesmero et al 2007Sesmero et al , 2009Meli et al 2010).It was found that a primary alcohol such as hexanol, and an aldehyde such as hexanal were potent inhibitors of PLD activity (Paliyath et al 1999). Hexanal was proven to be a more potent inhibitor, apparently due F o r R e v i e w O n l y to the lack of hydroxyl group that may interrupt the complete hydrolysis of substrate-enzyme intermediate.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, phospholipase D causes membrane deterioration through catalyzing the hydrolysis of phospholipids, which maintain cell viability and homeostasis into phosphatidic acid (Dawidowicz 1987;Exton 1997). Suppressing such enzymes in fruit tissues considerably reduces softening rate, improve fruit quality, and extend shelf life (Brummell et al 1999;Sesmero et al 2007Sesmero et al , 2009Meli et al 2010).It was found that a primary alcohol such as hexanol, and an aldehyde such as hexanal were potent inhibitors of PLD activity (Paliyath et al 1999). Hexanal was proven to be a more potent inhibitor, apparently due F o r R e v i e w O n l y to the lack of hydroxyl group that may interrupt the complete hydrolysis of substrate-enzyme intermediate.…”
Section: Introductionmentioning
confidence: 98%
“…Tomato is a climacteric fruit, and ethylene is required for normal ripening (Alexander and Grierson, 2002). The advanced RNA interference technique is an efficient method for downregulating the genes involved in ethylene biosynthesis as well as enzymes that degrade the cell wall (Carrari et al, 2007) to extend the shelf life of tomato (Kramer and Redenbaugh, 1994;Xiong et al, 2005;Batra et al, 2010;Meli et al, 2010). However, genetically modified crops are not marketable worldwide owing to environmental safety issues and social acceptance (Qaim, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that IR constructs of transgenes can effectively induce RNA silencing to trigger knockout of specific gene expressions (Ali et al, 2010;Allen et al, 2004;Gavilano et al, 2006;Johansen and Carrington, 2001;Kusaba et al, 2003;Liu et al, 2002;Meli et al, 2010;Pandolfini et al, 2003;Segal et al, 2003;Smith et al, 2000;Xiong et al, 2005). In addition, a number of studies showed that IR constructs of transgenes containing virus-derived sequences transformed to plants can effectively protect plants from challenging viruses (Abhary et al 2006;Bucher et al 2006;Chen et al, 2004;Di Nicola-Negri et al 2005;Hammond et al 2006;Lennefors et al 2006;Pooggin et al 2003;Simón-Mateo and García, 2011;Tenllado et al 2003;Tenllado et al, 2004;Vanitharani et al, 2003;Wang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%